ANALISIS SIMULTAN ANTARA ALIRAN MODAL, NILAI TUKAR DAN INFLASI DI INDONESIA PERIODE 2000.01 – 2012.09 - Mardiansyah .; Dian Octaviani, ME (Media Ekonomi, 2013)
Globalization and the open economic enchanced the integration of financial market and the economic condition in several countries. The effects of such integration shows in the movement of capital flows between countries. The potential risks of the capital flows, such as sudden reversal, the pressure on the exchange rate and high inflation and the susceptibility on financial sector, might be be arised. The goal of this research is to analyze the relationship between capital flows, exchange rates and inflation in Indonesia period 2000.01 – 2012.09. The method used in this research is simultaneous equations method. The model equations in this study are divided into two, which are a short-term investments are proxied from portfolio investment and long-term investments proxied from foreign direct investment. The results of the first model estimates the short-term investments shows that the exchange rate and inflation does not significant affecting short-term investments, but the ratio of domestic interest rates to foreign interest has a positive and significant impact on short-term investments. While, a short-term investments has negative and significant impact on exchange rate IDR per USD and inflation positive and significant effect on exchange rate. Factors affecting the rate of inflation is SBI interest rate and the money supply. One the other hand, the results of the second model estimation shows that the exchange rate and inflation has positive and significant impact on the flow of foreign direct investment. Inflation rate does not alter the terms of the investor’s decision in investing in Indonesia, because it was followed by the improvement in economic conditions in Indonesia.Keywords: Capital Flows, Exchange Rate, Inflation, Simultaneous Equation